2020
DOI: 10.3390/ijerph17051575
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Caesarean Section Rates Using the Robson Classification System at a University Hospital in Spain

Abstract: Background: The WHO recommends the use of the Robson ten-group classification system (RTGCS) as an effective monitoring and analysis tool to assess the use of caesarean sections (CS). The present study aimed to conduct an analysis of births using the RTGCS in La Ribera University Hospital over nine years and to assess the levels and trends of CS births. Methods: Retrospective study between January 1, 2010, and December 31, 2018. All eligible women were allocated in RTGCS to determine the absolute and relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
5
16
0
4
Order By: Relevance
“…The WHO indicates that its ideal rate must range between 10% and 15% [ 27 ]. According to the present study, Spain easily exceeds the recommended rate, and similar data also appear in other reports or studies [ 15 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The WHO indicates that its ideal rate must range between 10% and 15% [ 27 ]. According to the present study, Spain easily exceeds the recommended rate, and similar data also appear in other reports or studies [ 15 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…This rate is consistent with previous reports [9,17,18]. It has been suggested by Robson that a ratio between group 1 and 2 lower than 2:1 suggests a higher incidence of induction and CD before labour [19].…”
Section: Plos Onesupporting
confidence: 93%
“…A similar study was conducted in Peru from 2000 to 2010 and it was observed that group I and III along with Group V and VII were the major contributor to the increasing rate of CS. 15 There was another study conducted in Spain in the year 2010 and result was similar to our study with Group I (20.4%) and Group II (29.4%) as a second major contributor to increasing CS rate after group V. 16 Based on our study and the results of other studies across the world we believe 3 major concerns need to be addressed to limit the increasing CS rate. The first and the most critical is that every hospital should adopt clear guideline regarding induction of labour.…”
Section: Discussionsupporting
confidence: 87%